Optimization of hydrogen production from agricultural wastes using mixture design - Shuang, Liu; Chunying, Wang; Lili, Yin; Wenzhe, Li; Zhongjiang, Wang; Lina, Luo (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Hydrogen production from food waste, cattle manure, potato pulp and pig manure was optimized through using mixture design in this study. The synergic and antagonistic effects of the four substrates on hydrogen yield, substrate conversion efficiency and pH were evaluated. The results showed that the optimal proportion of food waste, cattle manure, potato pulp and pig manure were 61.6%, 38.4%, 0, and 0, respectively. Under the optimal condition, hydrogen yield of 21.0 mL/g VS with VS reduction of 29.4% and pH of 5 could be obtained. The interaction between food waste and cattle manure had strongest synergistic effects. Hydrogen was mainly produced by acetic-butyric metabolic pathway, and ammonification of protein played an important role in the maintenance of pH.Keywords: hydrogen, biohydrogen production, agricultural waste, dark fermentation, mixture designDOI: 10.3965/j.ijabe.20171003.2688Citation: Liu S, Wang C Y, Yin L L, Li W Z, Wang Z J, Luo L N. Optimization of hydrogen production from agricultural wastes using mixture design. Int J Agric & Biol Eng, 2017; 10(3): 246–254.